Prevalence of Helicobacter pylori among patients with dyspepsia and correlation between endoscopic and histological diagnosis (Journal of Pathology of Nepal, 2016)
Background: Dyspepsia is a prevalent complaint in general practice and gastrointestinal clinics. Helicobacter pylori have major causal relationship with gastro duodenal disease. The following study seeks to identify the prevalence of H. pylori based on histology and to correlate endoscopic findings with histopathology.Materials and Methods: This was a cross-sectional observational study conducted in GRP Polyclinic and Om Hospital and research centre from April 2015-September 2015. The upper gastrointestinal endoscopic findings were recorded and were correlated with histopathological findings. All the relevant data were collected and analysed using Statistical Package of Social Sciences version 16 for windows.  Results: Endoscopy finding was divided into reflux esophagitis, antral gastritis, duodenitis, duodenal ulcer, gastric ulcer, and gastric cancer. Duodenal ulcer and gastric ulcer was noted more frequently in males than in females (55.0% vs. 45.0% and 58.2% vs. 41.8%), respectively, P < 0.001).Chronic follicular gastritis was the most common in gastric ulcer (41.7%), whereas chronic persistent gastritis was common in non-ulcerative disease. Chronic active gastritis and chronic follicular gastritis were more common in ulcerative diseases, whereas chronic persistent gastritis was more common in gastritis and duodenitis (P < 0.001). The overall prevalence of H. pylori infection was 68.1% with male preponderance. Chronic active gastritis had highest prevalence of H. pylori (84.8%), followed by chronic follicular gastritis (84.1%) and chronic persistent gastritis (p value < 0.001.Conclusion: Rate of H. pylori infected patients with dyspepsia was high. Ulcerative lesions were more common in males than in females with higher rate of infection with H. Pylori.  Histological diagnosis of chronic active gastritis and chronic follicular gastritis was the most common pathologies in ulcerative lesions.